A multicenter, retrospective, case‐cohort study of the epidemiology and risk factors for Clostridium difficile infection among cord blood transplant recipients. Issue 4 (12th July 2017) - Alonso, Carolyn D.; Braun, David A.; Patel, Ishan; Akbari, Mona; Oh, Daniel Jungmyung; Jun, Tomi; McMasters, Malgorzata; Hammond, Sarah P.; Glotzbecker, Brett; Cutler, Corey; Leffler, Daniel A.; Ballen, Karen K.; et al.
Abstract: Background: Clostridium difficile infection (CDI) is the leading cause of health‐care associated infectious diarrhea. The aim of this study was to evaluate the epidemiology and risk factors for CDI in the 100 days following umbilical cord blood transplantation (UCBT) at three Boston hospitals. Methods: We performed a multicenter, retrospective, case‐cohort study of 226 UCBT recipients at Beth Israel Deaconess Medical Center, Massachusetts General Hospital, and Dana Farber/Brigham and Women's Cancer Center from 2003 to 2012. CDI was defined as diarrhea (≥3 unformed bowel movements for at least 2 days) plus a positive stool test for toxinogenic C. difficile and not attributed to any other cause. Results: Among 226 UCBT recipients, 22 patients (9.7%) developed CDI within the first 100 days of transplant (corresponding to an infection rate of 10.8 cases per 10 000 person‐days). The 100‐day and 1‐year rates were stable across the time period and between institutions. UCBT recipients with CDI were more likely than non‐CDI patients to be older, with higher body mass indices, and to have received an antipseudomonal penicillin agent. In a time‐dependent case‐cohort analysis of the risk factors associated with CDI in the first 100 days after UCBT, bacterial infection after UCBT was the strongest risk factor for CDI (hazard ratio 2.8; 95% confidence interval 1.08‐7.24; P =.03), after adjustment for transplant variables including antibiotic exposure. Conclusion: This study verifies the previously reported risk factors for CDI including older age and antibiotic exposure and identifies a novel association between bacterial infections and risk for CDI.